Contemplation, Subcreation, and Video Games - Mark J. P. Wolf (Religions, 2018)
This essay asks how religion and theological ideas might be made manifest in video games, and particularly the creation of video games as a religious activity, looking at contemplative experiences in video games, and the creation and world-building of game worlds as a form of Tolkienian subcreation, which itself leads to contemplation regarding the creation of worlds.